Primary care-led dementia diagnosis services in South Gloucestershire: Themes from people and families living with dementia and health care professionals. (November 2016) - Dodd, Emily; Cheston, Richard; Cullum, Sarah; Jefferies, Rosalyn; Ismail, Sanda; Gatting, Lauren; Fear, Tina; Gray, Richard
Background: Primary care-led dementia services are an increasingly common form of service delivery; however, little is known about how these services are understood by their main stakeholders: the patients, family members and health care professionals. A primary care-led dementia service was piloted in the South Gloucestershire area during 2012, in which general practitioners (GPs) led the process of assessment and establishing a diagnosis. Of the 26 surgeries in the area, 11 initially agreed to participate in the pilot, with 12 more joining the project by the end of December 2012. Aim: The aim of this study was to provide a qualitative analysis of the experiences of health care professionals, patients and their families, of the new process of assessment, diagnosis and treatment of dementia within a primary care service. Methods: Four patients, three care-givers and eight health care professionals were interviewed by peer researchers – all of whom were current care-givers. Interviews were transcribed and analysed using thematic analysis following Braun and Clarke's model. Data were also gathered about the number of referrals and what happened to these referrals. Results: Themes gathered into four main areas: ' the journey', 'what next?', 'the benefits and limits of primary care' and 'are GPs getting it right'? Conclusions: The analysis provided a perspective on the experiences of patients, family members and health care professionals involved in the relocation of part of the memory service, from secondary care (memory clinics) to primary care, being piloted in South Gloucestershire. This identified both practical issues to be improved upon as well as possible barriers.